2017
DOI: 10.1128/jcm.01232-16
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Testing Considerations: Lessons Learned from the First 80 Real-Time Reverse Transcription-PCR-Positive Cases Diagnosed in New York State

Abstract: The performance and interpretation of laboratory tests for Zika virus (ZKV) continue to be evaluated. Serology is cross-reactive, laborious, and frequently difficult to interpret, and serum was initially solely recommended for molecular diagnosis. ZKV testing was initiated in January 2016 in New York State for symptomatic patients, pregnant women, their infants, and patients with Guillain-Barré syndrome who had traveled to areas with ZKV transmission. Subsequently, eligibility was expanded to pregnant women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
1
27
2
2
Order By: Relevance
“…6. The interpretation of serological results is further complicated by the lower antibody titers in Zika disease than in dengue, perhaps because serum ZIKV loads are also very low (45).…”
Section: Discussionmentioning
confidence: 99%
“…6. The interpretation of serological results is further complicated by the lower antibody titers in Zika disease than in dengue, perhaps because serum ZIKV loads are also very low (45).…”
Section: Discussionmentioning
confidence: 99%
“…Blood serum is usually the preferred specimen choice for detection of ZIKV through either antibody-based serological methods or molecular diagnosis of viral RNA. But low-level viremia and collection of serum 10 days after the onset of symptoms may limit the sensitivity of molecular methods (St. George et al 2017;Theel and Hata 2018). However, the comparative analysis of different specimen types showed higher viral loads in urine samples (St. George et al 2017).…”
Section: Diagnosismentioning
confidence: 99%
“…But low-level viremia and collection of serum 10 days after the onset of symptoms may limit the sensitivity of molecular methods (St. George et al 2017;Theel and Hata 2018). However, the comparative analysis of different specimen types showed higher viral loads in urine samples (St. George et al 2017). In addition to serum and urine, body fluids like amniotic fluid, saliva, cerebrospinal fluid, semen, and placental tissue can also be used as specimen for ZIKV detection (Gourinat et al 2015;Musso et al 2015b;Atkinson et al 2016;Staples et al 2016).…”
Section: Diagnosismentioning
confidence: 99%
“…As for other flaviviruses [232,233], YFV RNA can be detected in urine and semen but unfortunately, we lack reliable data on the frequency of detection of the virus in urine/semen samples. The closely related ZIKV is detected in urine with a 50-95% frequency [234][235][236][237] and in semen in up to 33% [233] of confirmed male cases. Noteworthy, prolonged detection of ZIKV RNA was reported in urine/semen as compared to serum [234,235,237,238], with semen being tested positive up to six months after the onset of symptoms [239].…”
Section: Virus Tracking: Diagnostic Tools Inventorymentioning
confidence: 99%
“…The closely related ZIKV is detected in urine with a 50-95% frequency [234][235][236][237] and in semen in up to 33% [233] of confirmed male cases. Noteworthy, prolonged detection of ZIKV RNA was reported in urine/semen as compared to serum [234,235,237,238], with semen being tested positive up to six months after the onset of symptoms [239]. On this basis, it has been suggested that testing urine might improve molecular ZIKV detection [234,235].…”
Section: Virus Tracking: Diagnostic Tools Inventorymentioning
confidence: 99%